2013
DOI: 10.1016/j.jhealeco.2013.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Plan selection in Medicare Part D: Evidence from administrative data

Abstract: We study the Medicare Part D prescription drug insurance program as a bellwether for designs of private, non-mandatory health insurance markets, focusing on the ability of consumers to evaluate and optimize their choices of plans. Our analysis of administrative data on medical claims in Medicare Part D suggests that fewer than 25 percent of individuals enroll in plans that are ex ante as good as the least cost plan specified by the Plan Finder tool made available to seniors by the Medicare administration, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
76
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 32 publications
9
76
0
Order By: Relevance
“…Unfortunately, there is evidence that individuals are usually at risk for making poor choices when it comes to health insurance (1). Although exchanges in Medicare Part D, for example, are considered a success in terms of achieving high enrollment rates (2, 3), recent analysis on plan choice and drug claims shows that the majority of enrollees ignore Medicare's readily available plan recommendations, and choose plans that fail to minimize their expected costs based on current drug needs, health status, and health risks (4,5). Moreover, consumers have been shown not to understand traditional health insurance plans (6).…”
Section: -44mentioning
confidence: 99%
“…Unfortunately, there is evidence that individuals are usually at risk for making poor choices when it comes to health insurance (1). Although exchanges in Medicare Part D, for example, are considered a success in terms of achieving high enrollment rates (2, 3), recent analysis on plan choice and drug claims shows that the majority of enrollees ignore Medicare's readily available plan recommendations, and choose plans that fail to minimize their expected costs based on current drug needs, health status, and health risks (4,5). Moreover, consumers have been shown not to understand traditional health insurance plans (6).…”
Section: -44mentioning
confidence: 99%
“…Although open enrollment periods occur each year when people can switch plans, almost no one does, consistent with the status quo bias so commonly found in behavioral economic studies. Yet, switching to a cheaper plan could save on average ∼$300-500 per year (1,14,21). Similarly, research by Heiss and colleagues demonstrated that it could also save Medicare billions of dollars per year because the program subsidizes 75% of premium costs.…”
Section: Wwwannualreviewsorg • Behavioral Economics Of Healthmentioning
confidence: 99%
“…Some studies have found that while seniors appreciate being able to choose from a variety of plans, they do not feel confident in their ability to do so and want the selection process to be easier (11). People are often not enrolled in the plan that would cover their drugs at the lowest price (12,13) and rarely change plans even when there are alternatives that provide ex ante coverage at a lower cost (14,15).…”
Section: Introductionmentioning
confidence: 99%